Questions on the Georgian translation of the Acts of the Apostles - Agnès Ouzounian (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Without claiming to answer the question of knowing from which language, Greek or Armenian, was translated the text of the Acts of the Apostles into Georgian, I would just draw attention to few linguistic events noted during a comparative reading of the Acts in its three variants – Greek, Georgian and Armenian. Three points will be discussed here; the first two involve the Georgian and Armenian versions of the Acts, the third one involve the Georgian and Greek texts.